Homogeneous gold catalysis: mechanism and relativistic effects of the addition of water to propyne - Lein, Matthias; Rudolph, Matthias; Hashmi, A. Stephen K.; Schwerdtfeger, Peter (Organometallics, 2010)
Homogeneous catalysis employing gold compounds is a rapidly developing field. Au(III) catalysts in particular are interesting, since they exhibit catalytic properties unseen in other metals. In this study we report for the first time the complete mechanism of the nucleophilic addition of water to triple bonds that have not specifically been activated. The effect that the coordination of solvent molecules has on the course of the catalytic cycle is demonstrated, and the importance of hydrogen bonds to guide the substrate through the mechanism is highlighted. The influence of relativistic effects, which are particularly important for very heavy metals such as gold, is investigated, and it is concluded that the catalytic activity of gold could be seen as a relativistic effect.
Gesehen am 13.03.2023